IMIGRAN CINA: PERANANNYA DALAM SEJARAH PERDAGANGAN DI INDONESIA - Andi Nuralang (BRIN, 2002)
The Chinese ethnic group in Indonesia is often identified as a group that has an important role in the world economy in Indonesia. Although in fact not all Chinese people have talent in the business world. Based on archaeological evidence found in Indonesia, it indicates that ethnic Chinese had triumphed in Indonesia and even now. This group formed settlements in various regions in Indonesia with trading activities, became mining workers, and had Indonesian Chinese ancestry. The domination of the economy by Chinese migrants is a mirror for Indonesia to move forward.